EPIDEMIOLOGY OF NON-GRAVID METRORRHAGIA AMONG DIFFERENT GROUPS OF THE POPULATION OF WOMEN IN ANDIZHAN (BASED ON A 15-YEAR RETROSPECTIVE STUDY) - N.S Mamasaliev; Sh.M Nuritdinova; Kh.Kh.; Tursunov; Z.N. Mamasaliev; B.U Usmonov (Journal of modern medicine, 2026)
Despite significant advances in emergency obstetrics and gynecology, urgent nongravid metrorrhagia (UNGM) remains one of the most understudied acute problems, particularly its epidemiological and emergency preventive aspects. Epidemiological and emergency diagnostics are required in virtually all urgent (comorbid) clinical situations. This is crucial for the early development of optimized algorithms for preclinical diagnosis and prevention, as well as for the targeted determination of emergency medical care strategies and subsequent emergency investigations for UNGM.Key words: bronchial asthma, chronic obstructive pulmonary disease, bronchial obstruction, epidemiology, prevention, treatment.The global prevalence of UUU remains unknown. The literature presents only statistical, rather than epidemiological, data, which demonstrates that the overall clinical situation with UUU across various regions of the world is unfavorable: 1 million women annually seek emergency medical care due to certain forms of UUU. For example, with the most common types—heavy menstrual bleeding (HMB) or abnormal uterine bleeding (AUB), the risk of emergency hospitalization more than doubles. In other countries, every second woman with UUU does not seek medical care, and they live with a high risk of developing an "obstetric continuum" (increased mortality due to existing comorbidities) and/or this condition increases the frequency of surgical interventions. More than 50% of women of reproductive age experience abnormal uterine bleeding at least once in their lives.